Dubbing animation into Spanish: behind the voices of animated characters - Sofía Sánchez Mompeán (JoSTrans: The Journal of Specialised Translation)
In response to the burgeoning growth that the animation market has witnessed in recent years and to the competitive rivalry that exists within the industry, the presence of celebrity voices in animated movies is increasingly regarded as an effective strategy to broaden audience appeal. This paper attempts to determine if the use of celebrities in the original version may somehow influence the way the target text is dubbed in foreign markets. A clean-cut distinction between two key concepts that are sometimes overlapped, voice acting and dubbing, will not only provide the perfect backdrop for the upcoming sections, but will also offer useful context to understand their theoretical and practical limitations. The data under study will illustrate the current panorama within the Spanish dubbing framework by comparing the presence of both celebrities and dubbing actors in those Hollywood blockbusters released in Spain from 2007 to 2013. The results obtained suggest that some of the strategies used in the dubbed version might indeed be prompted by the original voicing.